Taking care of grafted seedlings of avocado and mango fruits - International Livestock Research Institute (International Livestock Research Institute, 2012)
Programme Narrator (Introduction): The objective of this broadcast entitled ‘our farming’ is to motivate our people to get introduced to new farming techniques of contemporary period, produce improved yield to improve their living standard.